(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Acne is one of the most common skin conditions. Acne scars are usually leading to disfigurement and psychosocial problem. Objective: To evaluate the efficacy and safety of carbon dioxide CO2 fractional laser and to evaluate the efficacy and safety of growth factor solution when is used in constant with CO2 fractional laser in the treatment of old severe acne scarring. Methods: Twenty seven patients were divided in to three groups according to their ages and scarring ages. Group l & ll were treated by CO2 fractional laser only. Group lll were treated by CO2 fractional laser plus growth factor. A period of six-month follow-up was done after the last session. Responses to the treatment were graded on quartile grading scale. Results: Near total improvement was observed in group l age (18-25 years), only (3) of them had marked improvement > 50% after 3 laser sessions. Group ll, age (32-50 years), after 6 laser sessions (6) patient had (grade ll) moderate improvement, (2) of them minimal improvement. Group lll, age (32-45 years) after 6 laser sessions, two patients had (grade lV) > 75%, (5) of them (grade lll) 51- 75% marked improvement. Conclusion: Newly formed acne scarring in young patient responds and improved well to CO2 fractional laser. Growth factor complex increased the improvement in old acne scarring. Keywords: Acne, scars, fractional CO2, laser, growth factor complex solution